Effect of Temperature, Catalyst Concentration and Time, on Polylactic Acid Production from Sisal Boles Juice by Ring Open Polymerization - Msuya, Neema; Temu, Abraham K.; Minja, Rwaichi J. A. (Tanzania Journal of Engineering and Technology, 2022)
Polylactic acid (PLA) is a biodegradable and renewable alternative to non-biodegradable petrochemical-based polymers that is environmentally friendly and green. PLA can be made from a variety of agricultural wastes that contain sugars, such as sisal boles. This study aimed at analysing the possibility of producing PLA from lactic acid (LA) produced from sisal bole. A 2n factorial design was used to analyse the effects of temperature (160-180 ºC), time (1-2 hrs) and tin octoate catalyst concentration (0.025-0.05%) on the PLA yield during polymerization. Minitab Version 20.2.0 was used to design the experiment and analyse the effects on the responses through ANOVA. It was possible to produce 0.73 ±0.05 g of lactide per g of sisal bole LA used. More than 99% conversion of lactide into PLA was done for 2 hrs when the system temperature was 180 ºC regardless of the catalyst ratio used. Temperature and time significantly affected the yield with p-values of less than 0.05 at 95% confidence level. The current findings support sisal bole juice as an alternative feedstock for LA production, a precursor for PLA. The use of sisal bole (SB) waste will protect environment by using waste biomass as an opportunity to participate in a global move to produce biobased plastics and promote the ban on the use of petrochemical-based plastics in packaging. Keywords: PLA production, Poly (lactic-acid), PLA characterization, Sisal bole.